Distinct effects of in-situ and ex-situ hydrogen charging methods on the mechanical behavior of CoCrFeNi high-entropy alloy fabricated by laser-powder bed fusion - Lee, Dong-Hyun (2023)
The hydrogen embrittlement behavior of CoCrFeNi high-entropy alloy (HEA) fabricated by laser-powder bed fusion (L-PBF) under ex-situ and in-situ hydrogen charging conditions was investigated. The ex-situ hydrogen pre-charged sample showed excellent resistance to hydrogen embrittlement, whereas in-situ hydrogen charging during tensile testing led to a substantial loss in ductility and prevailing hydrogen-assisted cracking. Such discrepancy was attributed to the enhanced apparent solubility and diffusivity especially at grain boundaries in the in-situ condition. The underlying hydrogen embrittlement mechanisms for the current L-PBF HEA are discussed, through which the critical role of the synergy between mechanical and environmental conditions is highlighted.